Identification of opaque black bean recombinant lines resistant to BCMV, BCMNV and BGYMV using molecular markers - Anaya-López, José Luis; Garrido-Ramírez, Eduardo Raymundo; Chiquito-Almanza, Elizabeth; Tosquy-Valle, Oscar Hugo; Ibarra-Pérez, Francisco Javier; López-Salinas, Ernesto (Revista Mexicana de Ciencias Agrícolas, 2018)
The opaque black bean from the Mesoamerican collection is consumed and produced in Mexico. To identify recombinant lines of opaque black bean resistant to bean common mosaic virus (BCMV), mosaic virus and common bean necrosis (BCMNV) and bean golden yellow mosaic virus (BGYMV), during 2015 and 2016 a collection of 70 genotypes that included 20 varieties and 50 recombinant lines (LR) was evaluated. The LRs derived from three different crosses: ‛Negro Papaloapan’/SEN-46, ‛Negro Citlali’/XRAV-187-3 and ‛Jamapa Plus’/XRAV-187-3. All genotypes were inoculated with the strains BCMNV NL-3 and BGYMV-MX, and were genotyped with the molecular markers SW13, ENM, SBD5 and SR2 linked to the resistance genes I, bc-3, bc12 and bgm-1. The 21 LR were identified with plants that had the genes bgm-1, I, or the combination I + bc-3 and broad-spectrum or specific resistance to BCMV, BCMNV and BGYMV. All the LRs had a high proportion of plants with the I gene. Six LRs derived from the cross ‛Negro Papaloapan’/SEN-46 and two from each of the crosses ‛Negro Citlali’/XRAV-187-3 and ‛Jamapa Plus’/XRAV-187-3 had between 8% and 92% of plants with the genetic combination I + bc-3 that confers resistance to BCMV and BCMNV. While the genes I and bgm-1, which confers resistance to BCMV and BGYMV, were detected in three LRs of the ‛Negro Papaloapan’/SEN-46 and four of ‛Negro Citlali’/XRAV-187-3 crosses. Four LR derived from the cross ‛Negro Papaloapan’/SEN-46: ‛Negro Papaloapan’/SEN 46-7-8, ‛Negro Papaloapan’/SEN-46-7-11, ‛Negro Papaloapan’/SEN-46-7 -12 and ‛Negro Papaloapan’/SEN-46-7-13 had plants with the I, bc-3 and bgm-1 genes that confers broad-spectrum resistance to BCMV, BCMNV and BGYMV. The heterogeneity of the LR in the proportion of plants with the resistance genes, highlights the need to implement selection strategies assisted by molecular markers to homogenize them, and develop opaque black bean varieties with resistance to three of the viruses that most affect bean production in Latin America.
Keywords: Phaseolus vulgaris L.; bc-3; bgm-1; eIF4E2; SAMM